2017
DOI: 10.1039/c7ob00142h
|View full text |Cite
|
Sign up to set email alerts
|

N 1-Selective alkenylation of 1-sulfonyl-1,2,3-triazoles with alkynes via gold catalysis

Abstract: A N-selective alkenylation of 1-sulfonyl-1,2,3-triazoles with alkynes via gold catalysis is reported. N-Vinyl substituted 1,2,3-triazoles were selectively prepared in up to 92% yield through the sulfonyl group of 1,2,3-triazole derivatives transformed to alkenyl groups in a "one-pot two steps" manner. This method provided a new method for the synthesis of potentially biological-active vinyl-triazole building blocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…3h 4-Substituted-1 H -1,2,3-triazoles have been shown to be useful in coordination chemistry, 4 e.g., the bis(1,2,3-triazol-4-yl)pyridine motif was demonstrated as a versatile tridentate ligand for supramolecular and coordination chemistry 4a and as a ligand for ruthenium in dye-sensitized solar cells. 4b NH-triazole is also a convenient scaffold for further modifications, e.g., N 2 -selective modifications into 2,4-disubstituted triazoles, 5 halogenation at the C-5 position of the triazole, 6 N 1 -oxidative C–N bond coupling with quinoxalinone 7 and pyrroles, 8 gold-catalyzed N 1 -selective alkenylation, 9 and for the preparation of 1,2,3-triazolide ionic liquids. 10 …”
Section: Introductionmentioning
confidence: 99%
“…3h 4-Substituted-1 H -1,2,3-triazoles have been shown to be useful in coordination chemistry, 4 e.g., the bis(1,2,3-triazol-4-yl)pyridine motif was demonstrated as a versatile tridentate ligand for supramolecular and coordination chemistry 4a and as a ligand for ruthenium in dye-sensitized solar cells. 4b NH-triazole is also a convenient scaffold for further modifications, e.g., N 2 -selective modifications into 2,4-disubstituted triazoles, 5 halogenation at the C-5 position of the triazole, 6 N 1 -oxidative C–N bond coupling with quinoxalinone 7 and pyrroles, 8 gold-catalyzed N 1 -selective alkenylation, 9 and for the preparation of 1,2,3-triazolide ionic liquids. 10 …”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Zhao and colleagues described an efficient protocol for the synthesis of 1-α-substituted vinyl-1,2,3-triazoles 59 via hydroamination in one-pot two-step manner. [25] This protocol, initiated by desulfonylation of NTs-1,2,3-triazoles 57 with 2.0 equiv. of H 2 O in DCE, followed by nucleophilic addition of in situ generated NH-1,2,3-triazoles with different inactivated terminal alkynes 58 in the presence of IPrAuCl (5 mol%) and AgOTf (5 mol%) in DCE at 80°C, furnished the corresponding 1-VT products 59 in 25 to 92% yields (Scheme 20).…”
Section: Synthesis Of 1-vts Through Hydroamination Of Alkynes With Nhmentioning
confidence: 99%
“…of H 2 O in DCE, followed by nucleophilic addition of in situ generated NH-1,2,3-triazoles with different inactivated terminal alkynes 58 in the presence of IPrAuCl (5 mol%) and AgOTf (5 mol%) in DCE at 80°C, furnished the corresponding 1-VT products 59 in 25 to 92% yields (Scheme 20). [25] In 2014, Malekdar et al revealed a technique for the synthesis of 1-β-substituted vinyl-1,2,3-triazoles 62/63 via onepot microwave-assisted solvent-free hydroamination. Herein, 1,2,3-benzotriazole 60 and NH-1,2,3-triazole-4-carboxylic acid methyl ester 61 undergo nucleophilic addition with activated alkynes 58 assisted by MW 200 W in solvent-free system to furnish the desired 1-VT products 62 and 63 respectively, in 87-92% yields (Scheme 21).…”
Section: Synthesis Of 1-vts Through Hydroamination Of Alkynes With Nhmentioning
confidence: 99%
“…However, such approaches are complicated by a low energy barrier between the N 1 and N 2 tautomers in solution leading to poor N 1 / N 2 selectivity, for instance, in the direct N-alkylation of triazoles [21][22][23]. Despite these challenges, a number of N 1 -and N 2 -selective alkylation methods have been developed employing transition metal catalysts which include Au-catalysed desul- fonylative coupling N-tosyl-1,2,3-triazoles with alkynes and Rh catalysed N 1 and N 2 selective alkylations [24,25].…”
Section: Introductionmentioning
confidence: 99%